2024
DOI: 10.3390/medicina60020215
|View full text |Cite
|
Sign up to set email alerts
|

From Anxiety to Hardiness: The Role of Self-Efficacy in Spanish CCU Nurses in the COVID-19 Pandemic

Fernanda Gil-Almagro,
Fernando José García-Hedrera,
Francisco Javier Carmona-Monge
et al.

Abstract: Background and Objectives: Evidence shows that throughout the COVID-19 pandemic, nurses suffered from emotional symptoms, yet in spite of this, few studies within “positive psychology” have analyzed the emergence/promotion of positive traits, such as hardiness. In this context, the present study aimed to test a model regarding the mediating role of self-efficacy between anxiety experienced at the beginning of the COVID-19 pandemic and hardiness assessed six months later among nurses in critical care units (CCU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Recent research has found an association between self-efficacy and insomnia in the general population, in line with our results [ 60 , 61 ]. Meanwhile, specifically among nurses it has been found that in stressful work situations, self-efficacy acts as a clear protector in the management of anxiety and can even have positive consequences, such as the development of a resilient personality, if the anxiety derived from stressful work situations is managed through self-efficacy [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found an association between self-efficacy and insomnia in the general population, in line with our results [ 60 , 61 ]. Meanwhile, specifically among nurses it has been found that in stressful work situations, self-efficacy acts as a clear protector in the management of anxiety and can even have positive consequences, such as the development of a resilient personality, if the anxiety derived from stressful work situations is managed through self-efficacy [ 62 ].…”
Section: Discussionmentioning
confidence: 99%